AGRIBUSINESS INSTITUTIONS IN THE PANDEMIC TIME COVID -19: A LESS CONTACT ECONOMIC APPROACH. - KENAL P HUTAPEA; DONNY IVAN SIMATUPANG (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
Business construction in the era of the global covid-19 pandemic has definitely changed. The reduction of physical contact is the most demanding health protocol. For the agricultural or agribusiness industry, this certainly reduces business performance significantly. The study aims to identify agribusiness institutions in the era of the Covid-19 pandemic. The research method uses descriptive qualitative methods to describe the institutional and agro-business development models in the current pandemic era. Primary data obtained from various literature are representative and describe the actual condition. The results showed that the role of a synergistic institution is needed in every agribusiness subsystem, to help solve problems at the farm, marketing and agro-industry levels. A technological approach to digital marketing is needed as a form of modification of agribusiness institutions at this time.